Answer:
Step-by-step explanation:
Factoring will reveal the solution. So we divide the equation by the greatest common factor of the terms and use that factor as the coefficient. In this case the greatest common factor is just x.
2x^2+5x
x(2x+5) so the equation will equal zero when either of those expressions is zero because zero times anything is zero. x=0 and x=-5/2
The expression - x - 9x^2 + 12x^2 + 7 has 4 terms:
-x, -9x^2, 12x^2, 7
Like terms are:
-9x^2, 12x^2
Answer:
x = -1
Step-by-step explanation:
AB + BC = AC = 28
the way from A to C goes through B.
so, the total way of A to C is the sum of the way from A to B and then from B to C.
=>
(5x + 10) + (2x + 25) = 28
7x + 35 = 28
7x = -7
x = -1
That one correct so yes um cause the app said answer must be above 20 characters
Answer:
r = √14
Step-by-step explanation:
Is this what you meant? If so heres' the answer
Equation of circle
Center the origin
r = √14